2011
DOI: 10.7763/ijapm.2011.v1.27
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of O2, CO2, NO2 and SO2 on Si- doped Carbon Nanotube

Abstract: Abstract-We report reactivity of silicon doped single walled carbon nanotube (Si-CNT) towards the small atmospheric gas molecules O 2 , CO 2 , SO 2 and NO 2 using density functional theory based on the numerical basis set method. The reactivity of gas molecules is explained with binding energy, band structure, charge density, and density of states. We found that the substitutional doping of silicon atom in CNT increases the binding energy as compared with pure CNT. The charge density analysis reveals the forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In addition to pristine CNT and BNNT, CBNNT also shows stronger O 2 adsorption ability than certain doped nanotubes, such as phosphorus‐nitrogen doped carbon nanotube (BE = −1.41 kcal mol −1 ) . However, it is weaker than the phosphorus doped carbon nanotube (BE = −17.43 kcal mol −1 ), silicon carbide nanotube (BE = −23.53 kcal mol −1 ), nitrogen doped carbon nanotube (BE = −17.07 kcal mol −1 ), nitrogen doped short carbon nanotube (BE = −59.27 kcal mol −1 ), and silicon doped carbon nanotube (BE = −60.58 kcal mol −1 ) . Nevertheless, there are likely possibilities for further tuning the O 2 adsorption ability of the CBNNT materials.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to pristine CNT and BNNT, CBNNT also shows stronger O 2 adsorption ability than certain doped nanotubes, such as phosphorus‐nitrogen doped carbon nanotube (BE = −1.41 kcal mol −1 ) . However, it is weaker than the phosphorus doped carbon nanotube (BE = −17.43 kcal mol −1 ), silicon carbide nanotube (BE = −23.53 kcal mol −1 ), nitrogen doped carbon nanotube (BE = −17.07 kcal mol −1 ), nitrogen doped short carbon nanotube (BE = −59.27 kcal mol −1 ), and silicon doped carbon nanotube (BE = −60.58 kcal mol −1 ) . Nevertheless, there are likely possibilities for further tuning the O 2 adsorption ability of the CBNNT materials.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, Si and N atoms of SN-rGOA can donate charge to the CO 2 and SO 2 molecule, which favorably interacts due to sharing lone pair of electrons of oxygen with Si and N atoms in SN-rGOA. 37 Delivered by Ingenta to: Guest …”
Section: Communicationmentioning
confidence: 98%
“…Furthermore, the band structure and density of states clearly illustrate the creation of an extra state near the Fermi level and reduction in the band gap, which acts as a reactive center for adsorption of the molecules on Si-CNT. 312 Ao et al investigated the enhancement of CO detection in Al-doped graphene using DFT calculations. 295 The results showed that CO molecules are only weakly adsorbed onto the intrinsic graphene with a small binding energy value and a large distance (d = 3.767 Å) between the CO molecule and graphene, whereas CO molecules strongly interact with the Al-doped graphene, forming an Al-CO bond (d = 1.964 Å) that introduces a large number of shallow acceptor states into the system.…”
Section: Adsorption Of Co Co 2 No 2 Nh 3 H 2 O and Omentioning
confidence: 99%